2019
DOI: 10.4293/jsls.2019.00046
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Hysterectomy Outcomes With and Without Robotic Assistance

Abstract: Objective:To evaluate the differences in operative time and postoperative complications for total laparoscopic hysterectomy (TLH) performed using conventional laparoendoscopic single-site surgery (LESS) versus a robotic-assisted LESS approach.Methods:A retrospective study was conducted of all cases of conventional LESS TLH (n = 47) and robotic LESS TLH (n = 129) for benign gynecologic conditions performed from November 2014 to October 2017. Patient characteristics, operative time for hysterectomy, estimated bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The clinical application of robotic assisted surgery has broadened significantly since the Food and Drug Administration approved the use of robotic platforms in gynaecologic surgery in 2005 10 . In the past 10 years, robotic surgery has made great progress in the field of minimally invasive surgery and has recently been applied to vNOTES 11–13 . However, unlike traditional vNOTES, robotic assisted vNOTES (R‐vNOTES) enables the use of wristed instruments, therefore improving the ability to proficiently suture and perform delicate pelvic dissection needed for complex surgery 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical application of robotic assisted surgery has broadened significantly since the Food and Drug Administration approved the use of robotic platforms in gynaecologic surgery in 2005 10 . In the past 10 years, robotic surgery has made great progress in the field of minimally invasive surgery and has recently been applied to vNOTES 11–13 . However, unlike traditional vNOTES, robotic assisted vNOTES (R‐vNOTES) enables the use of wristed instruments, therefore improving the ability to proficiently suture and perform delicate pelvic dissection needed for complex surgery 14 .…”
Section: Introductionmentioning
confidence: 99%
“…10 In the past 10 years, robotic surgery has made great progress in the field of minimally invasive surgery and has recently been applied to vNOTES. [11][12][13] However, unlike traditional vNOTES, robotic assisted vNOTES (R-vNOTES) enables the use of wristed instruments, therefore improving the ability to proficiently suture and perform delicate pelvic dissection needed for complex surgery. 14 Lee et al first reported 4 cases of R-vNOTES hysterectomy in 2015, suggesting that the use of the robotic platform in vNOTES hysterectomy is feasible and may have some advantages over traditional vNOTES.…”
mentioning
confidence: 99%
“…One RCT and a few observational studies that have looked at operative time for single port hysterectomy have found no significant difference in operative time when compared to multi-port hysterectomy [4,5,15]. A recent retrospective study looking at robotic single port surgery compared to conventional single port found an average decrease in operative time of 18 minutes that was statistically significant [16]. Expert single port surgeons have also demonstrated the feasibility of removing uteri as big as 20 weeks size when using articulating instruments [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is equivalent to the length of umbilical incision in robotic single hole laparoscopic surgery which length is 25~40 mm [22,23] . The existing literature [23][24][25] (the average follow-up time and the number of cases were 13.6 months, 1 month, 12 months and 12 cases, 7 cases, respectively, 129 cases) did not suggest an increase in complications such as infection of the umbilical incision and umbilical hernia after robotassisted single port laparoscopic surgery. In this study, the umbilical repair suture technique draws on the umbilical operation of TU-LESS.…”
Section: Query Of Tprtmentioning
confidence: 99%